Endoscopic Fenestration for Treating Galassi Type III Middle Cranial Fossa Arachnoid Cysts: Single- and Multiple-stoma have the Same Curative Effect - Zhu, Guang-tong; Li, Chu-zhong; Gui, Song-bai; Zhao, Peng; Li, Zhen-ye; Liu, Chun-hui; Zhang, Ya-zhuo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background For endoscopic fenestration of middle cranial fossa arachnoid cysts (MCFACs), the decisions on the location and number of stomas are key issues. However, research on this particular topic has been limited. Thus, this study aimed to compare single- versus multiple-stoma endoscopic fenestration for treating Galassi type III MCFACs.Methods This retrospective study included 86 patients with Galassi type III MCFACs treated with endoscopic fenestration. Single-stoma fenestration to the basal cistern was performed in 37 cases, whereas multiple-stoma fenestration to the basal cistern and the carotid cistern was performed in 49 cases. Clinicoradiologic profiles and follow-up data were analyzed.Results The rate of symptom relief was 83.7% (72/86), and the rate of cyst shrinkage was 96.5% (83/86). Postoperative ipsilateral subdural effusion, which was significant (p = 0.042), and noninfectious fever were the two most common complications in the single- and multiple-stoma groups. No significant differences in intraoperative nerve injury, vascular injury, proportion of cases with cyst reduction, and symptom remission rate were observed between the two groups. The rates of cyst recurrence and secondary surgery in the single-stoma group were higher than those in the multiple-stoma group, although the difference was not significant.Conclusion Endoscopic fenestration is an effective and minimally invasive approach for treating Galassi type III MCFACs. Single- and multiple-stoma endoscopic fenestrations have the same curative effect.
Keywords: arachnoid cysts; middle cranial fossa; neuroendoscopy; stoma; subdural; effusion